Wayne G. Borah papers - Borah, Wayne G., 1891-1966.
Case files, charges to juries, and reports of the U.S. Dept. of Justice examiners pertaining primarily to Borah's service (1928-1949) as judge on the U.S. District Court for the Eastern District of Louisiana. Case files relate chiefly to shipping disputes involving maritime vessels and railroad companies.
Lawyer and judge.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Formerly part of: J. Skelly Wright papers.
Keywords: United States. -- District Court (Louisiana : Eastern District); District courts -- United States; Freight and freightage -- United States; Railroads -- United States -- Traffic; Shipment of goods -- United States; Shipping -- United States; Jurists; Lawyers